2011
DOI: 10.1080/03602559.2010.543738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixing Process and Morphologies on the Electrical Conductivity of PA6/EVA/CB Composites

Abstract: Nylon6 (PA6)/Ethylene-(vinyl acetate) (EVA)/carbon black (CB) composites with different electrical conductivity were prepared in an internal mixer. The factors influencing the electrical conductivity of the ternary composites were investigated, including mixing mode, mixing time and mass ratio of PA6 and EVA, and so on. Among three kinds of PA6=EVA=CB composites, including ones prepared by directly mixing (composites A), EVA and CB were mixed prior to melt-compounding with PA6 (composites B) and PA6 and CB wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This is because the CB loose aggregates can work as imperfection sites inside the matrices, where cracks may readily start and propagate. For this reason most studies [3,[77][78][79] on polymers/CB composites (except elastomers) focused on improving electrical conductivity rather than mechanical performance. An electrical percolation threshold in general depends mainly on the CB structure and dispersion inside the matrices.…”
Section: Carbon Blackmentioning
confidence: 99%
“…This is because the CB loose aggregates can work as imperfection sites inside the matrices, where cracks may readily start and propagate. For this reason most studies [3,[77][78][79] on polymers/CB composites (except elastomers) focused on improving electrical conductivity rather than mechanical performance. An electrical percolation threshold in general depends mainly on the CB structure and dispersion inside the matrices.…”
Section: Carbon Blackmentioning
confidence: 99%
“…The use of immiscible binary polymer blends as the matrices has been proven to be a good method for tuning the distribution of conductive particles ever since the pioneering work of Sumita et al in 1991 [ 1 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. It is generally recognized that the formation efficiency of the conductive networks increases to a great extent, compared with single polymer as the matrix, when carbon fillers are selectively localized in one continuous polymer phase or at the interface of a cocontinuous-structured polymer blend, according to the double percolation mechanism [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from cocontinuous-structure, sea-island structure is another typical phase morphology of polymer blends. However, there are considerably less investigations involving the formation of conductive networks via interfacial localization of carbon fillers in sea-island-structured polymer blends [ 18 , 24 , 25 , 28 ] probably because the interface is not continuous throughout the entire blend and the inter-domain distance is usually far larger than the minimum inter-particle distance (10 nm) required in the average inter-particle distance model [ 30 ]. In the previous work by our research group [ 26 , 27 ], we found that CB can form highly-efficient conductive networks in sea-island-structured thermoplastic polyurethane (TPU)/polyamide copolymer (COPA) and nylon-poly(m-xylene adipamide) (MXD6)/poly(ethylene terephthalate) (PET) blends through thermodynamically-driven interfacial localization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fang et al [24] used EVA in the waste with the effect of crosslinking agent and catalyst to general physical modified the rough asphalt, so that the performance of asphalt have been significantly improved. Biodegradation Recycling.Biodegradation is also a method for biological recycling [25]. Biodegradable plastics can be decomposed by microorganisms in the environment.…”
Section: Recycling Methods Of Ppwmentioning
confidence: 99%